Organizational ESG practices and the attidudes of generation Z - Mrňová, Aneta (2024)
This thesis investigates Generation Z’s attitudes toward organizational ESG practices, aiming to bridge the gap in theoretical knowledge about ESG attitudes and provide practical implications for businesses. Employing an online questionnaire, quantitative data was collected from university students. Statistical analyses, including multiple regression, one-sample t-tests, one-way ANOVA, and correlation tests, revealed that Generation Z exhibits a high awareness of ESG, particularly valuing environmental aspects over governance. It was concluded that Generation Z displays an overall positive attitude toward organizational ESG practices shaped by the attributes of having a socially conscious mindset and a desire for authenticity. The research demonstrates a positive correlation between Generation Z's attitudes towards ESG and their inclination to pay premiums for sustainable products, as well as their consideration of ESG commitments when evaluating job opportunities. The managerial implications of the thesis highlight the necessity for companies to actively promote their ESG initiatives, as Generation Z’s perception of a company can be significantly influenced by its ESG practices. Thus, transparent communication and educational campaigns are essential to capitalize on aligning organizational ESG practices with Generation Z’s preference for environmentally and socially responsible brands.